TRANSLATION AND CULTURE:A CONTENT ANALYSIS OF INDONESIAN INFORMATION PORTAL WEBSITE - Dhea Tisane Ardhan (BASIS (Bahasa dan Sastra Inggris), 2020)
With the more rapid development of digital-based communication and information technology, people are forced to be able to work more quickly. Thereupon, the government is also obliged to give fast and responsive services in order to provide accurate information for the public. In Indonesia itself, the government has established the system of e-Government, by which one of the forms is a website. In order to accommodate global visitors, the website contents written from Bahasa Indonesia have to be shifted into English. Consequently, the process of translation is required. This study aims to analyze the English translation in the website of Indonesia Information Portal. Furthermore, this study also intends to investigate the aspects of localization and globalization throughout the website contents. Based on the examples of several findings, it can be viewed that in the English-translated pages of Indonesia Information Portal, some of the terms related to specific parliament system, worship places, and traditional food are not entirely translated. To sum up, the English translation in the website of Indonesia Information Portal can be considered to be adequately balanced and appropriate. The translator knows when to apply localization and when to apply globalization in translating several terminologies.